Quantitative analysis of traffic accidents in the city of Basra Using geographic information systems (GIS ) - Murtadha Muzaffar.Sahar /Ibraheem Hachem Lazim ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The problem of traffic accidents is one of the most important and complex contemporary human problems that many societies in this world suffer from, and to varying degrees from one society to another, as it is one of the causes of injuries or deaths resulting from collisions between vehicles or between vehicles and pedestrians, which result from exceeding the rules of And traffic systems from drivers or pedestrians, and therefore traffic accidents cause a lot of damage, whether economic, social or human. The research aims to study the quantitative analysis of traffic accidents in the city of Basra using geographic information systems, which amounted to (139) traffic accidents, representing 25.6% of the total traffic accidents in the urban centers of Basra Governorate, amounting to (541) accidents for the year 2022.